The practice of reaction window in an electrocatalytic on-chip microcell - Xia, Hang (2024)
To enhance the efficiency of catalysis, it is crucial to comprehend the behavior of individual nanowires/nanosheets. A developed on-chip microcell facilitates this study by creating a reaction window that exposes the catalyst region of interest. However, this technology's potential application is limited due to frequently-observed variations in data between different cells. In this study, we identify a conductance problem in the reaction windows of non-metallic catalysts as the cause of this issue. We investigate this problem using in-situ electronic/electrochemical measurements and atom-thin nanosheets as model catalysts. Our findings show that a full-open window, which exposes the entire catalyst channel, allows for efficient modulation of conductance, which is ten times higher than a half-open window. This often-overlooked factor has the potential to significantly improve the conductivity of non-metallic catalysts during the reaction process. After examining tens of cells, we develop a vertical microcell strategy to eliminate the conductance issue and enhance measurement reproducibility. Our study offers guidelines for conducting reliable microcell measurements on non-metallic single nanowire/nanosheet catalysts.